Assessment of public perception of electronic waste in Várzea – Rio Grande do Norte (RN), Brazil (Research, Society and Development, 2025)
The improper disposal of electronic waste (WEEE) has become a growing global challenge, directly affecting the environment and public health. In small municipalities like Jundiá, Rio Grande do Norte, this problem is exacerbated by the lack of adequate infrastructure, selective collection points, and effective public waste management policies. Given this scenario, this study aimed to assess the local population's perception of electronic waste, considering aspects related to disposal frequency, final disposal methods, and level of knowledge about the associated risks. The quantitative and descriptive study was conducted with 75 residents from urban and rural areas using structured questionnaires. The results showed that, although a significant portion of the population recognizes the risks of improper disposal, the predominant practice is still to dispose of WEEE in the regular trash, revealing a discrepancy between perception and action. It is concluded that there is an urgent need to intensify environmental education actions and implement specific collection points in order to promote more sustainable practices and align the local community with the guidelines of the National Solid Waste Policy.